Understanding Aktywność in Ethnographic Contexts: Aging, Memory, and Personhood in Poland - Jessica C. Robbins (University of Lower Silesia, 2013)
The increasing popularity of programs promoting aktywność (activity) in old age in contemporary Poland is part of regional and global attempts to encourage health and economic productivity in old age. In order to understand this interest in aktywność in old age, such practices must be seen within broader sociocultural and political-economic contexts. This drive for aktywność cannot be fully explained without understanding its status as an unquestioned moral good in opposition to illness, disability, and frailty in old age. Seeking commonalities across such seemingly opposite experiences can reduce marginalization in old age. Side-stepping binary constructions of health and illness in old age creates a more holistic perspective that demonstrates how older Poles in a range of contexts create moral lives.